PENGARUH MEDIA PEMBELAJARAN VISUAL DAN MEDIA PEMBELAJARAN KONVENSIONAL TERHADAP HASIL BELAJAR MATA PELAJARAN PKN SISWA KELAS VII A DAN B DI MTS AL JALY - Bahruddin; Sunardjo; Dian Eka Indriani (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
This research uses a quantitative research type of quasi experiment by using one variable to know the learning outcomes, namely, affective, cognitive and psychomotor, which aims to determine the effect and differences in visual learning media and conventional learning media on learning outcomes. Based on the data analysis, it is concluded that shows that citizenship education (PKn) learning with visual learning media is better than conventional learning media. There are differences in student learning outcomes after using with visual learning media in the subjects of Civics Class VII A MTs Al Jaly.